2019
DOI: 10.3390/insects10090262
|View full text |Cite
|
Sign up to set email alerts
|

Optical Modelling and Phylogenetic Analysis Provide Clues to the Likely Function of Corneal Nipple Arrays in Butterflies and Moths

Abstract: The lenses in compound eyes of butterflies and moths contain an array of nipple-shaped protuberances, or corneal nipples. Previous work has suggested that these nipples increase light transmittance and reduce the eye glare of moths that are inactive during the day. This work builds on but goes further than earlier analyses suggesting a functional role for these structures including, for the first time, an explanation of why moths are attracted to UV light. Using a phylogenetic approach and 3D optical modelling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…This lower reflection simultaneously indicates higher transmission of light into the eyes. This is also an advantage in low-light conditions, and comparative studies of nocturnal and diurnal lepidopterans have suggested that greater transmission of UV light from the moth-eye structure may be important for lepidopterans and cause attraction to UV lights [38]. Moreover, some other functions have been demonstrated for this structure.…”
Section: Nano-scale Nipple Arraymentioning
confidence: 99%
“…This lower reflection simultaneously indicates higher transmission of light into the eyes. This is also an advantage in low-light conditions, and comparative studies of nocturnal and diurnal lepidopterans have suggested that greater transmission of UV light from the moth-eye structure may be important for lepidopterans and cause attraction to UV lights [38]. Moreover, some other functions have been demonstrated for this structure.…”
Section: Nano-scale Nipple Arraymentioning
confidence: 99%
“…Additionally, Cordyceps militaris (L., 1758) (Hypocreales, Cordycipitaceae) was identified from C. pudibunda larvae and pupae (Nilsson, 1978;Sylvén, 1942). Spalding et al (2019) found that the corneal protrusions, which are thought to be an ancestral character of diurnal butterflies, are atrophied in C. pudibunda, suggesting specialization for night and a nocturnal life style adapted to low light intensity. This means that C. pudibunda is attracted to light.…”
Section: Pathogensmentioning
confidence: 96%
“…Spalding et al (2019) found that the corneal protrusions, which are thought to be an ancestral character of diurnal butterflies, are atrophied in C. pudibunda , suggesting specialization for night vision and a nocturnal life style adapted to low light intensity. This means that C. pudibunda is attracted to light.…”
Section: Managementmentioning
confidence: 99%
“… 34 In this direction, the analysis of chitin nanostructure in the eyes of butterflies and moths needs to be understood in detail. 35 38 …”
Section: Introductionmentioning
confidence: 99%
“…Better anti-reflective structures have paved the way for advanced manufacturing of moth-eye structures for various applications such as solar cells, light-emitting diodes, and display screens . In this direction, the analysis of chitin nanostructure in the eyes of butterflies and moths needs to be understood in detail. …”
Section: Introductionmentioning
confidence: 99%